Pengaruh E-Service Quality Terhadap Behavior Intentions Dengan E-Satisfaction Sebagai Mediator (Studi Pada Kriya.co.id) - Septi Agus Pratiwi; Citra Kusuma Dewi (Jurnal Computech & Bisnis (e-Journal), 2016)
The development of trade industry has grown rapidly, especially in online trading that facilitated by some e-commerce websites in Indonesia. With the increase of online transaction each year in Indonesia, then the start-up online businesses are competing to create an intermediary between sellers and buyers so that can conduct activities of these transactions easily. Some of the new websites that has been launched has each characteristic, one of that Kriya.co.id website is one of the e-commerce website for SMEs (Small and Medium Enterprises) in which a container of the SMEs in Indonesia to market products all over Indonesia. Kriya.co.id website is one of E-Commerce website for UKM in Indonesia that has products which have a unique and traditional value. Purpose of this research is for to knowing (1) the influence of E-Service Quality, E-Satisfaction dan Behavior Intentions in Kriya.co.id user. (2) The influence E-Service Quality of Behavior Intentions through E-Satisfaction Kriya.co.id user. This research methodology using a quantitative method consist of 100 respondents with descriptive research and causality. Sampling Technique use nonprobability sampling (purposive sampling). Technique data analysis used the path analysis. While the secondary data in this research has taken from various literature and relevant documents with the same as title and theme with this research. The results of path analysis are E-Service Quality doesn't influence towards Behavior Intentions so E-Service Quality doesn't influence towards Behavior Intentions with E-Satisfaction as a mediator because Behavior Intentions not determined by E-Service Quality of Kriya.co.id website, but E-Satisfaction that has been accepted by user after did the transaction.  E-Service Quality has a coefficient of  0,859 towards E-Satisfaction. E-Satisfaction has a coefficient of 0,636 towards Behavior Intentions. E-Service Quality has a coefficient of 0,167 towards Behavior Intentions. Keywords: behavior intentions, e-satisfaction, e-service quality.